The third Karmapa Rangjung Dorje: master of Māhamudrā - Gamble, Ruth (Lives of the masters, 2020)
The biography. Birth -- Education -- Retreat -- Teachings -- Death -- The writings. The Liberation Story of the In-Between State -- A Dream of Saraha -- A Mālā of Mountain Dharma's Siddhis -- "The Dancer," from One Hundred Birth Stories of the Teacher -- "King of the Nāgas," from One Hundred Birth Stories of the Teacher -- A Message to the Entire Kingdom -- Songs of the View, Cultivation, Behavior, and Result -- A Short Praise to surpu -- Song that Settles the Ground-of-All.